From the river to the sea Palestine and Israel in the shadow of "peace" - Turner, Mandy (Lexington Books, 2019)
This book analyses the impacts and responses to twenty-five years of "peace" between Israel and the Palestine Liberation Organization. It focuses on understanding the various political economies that have emerged and how different communities have developed distinct coping strategies as well as new forms of political expression and mobilization.